2023
DOI: 10.3390/jcm12062174
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Milieu on Dental Anxiety in Adolescents—A Cross-Sectional Study

Abstract: Parents play a significant role in the development of dental anxiety in their adolescent children. This cross-sectional study aimed to evaluate the influence of family milieu on adolescents’ dental anxiety. The level of dental anxiety (Dental Anxiety Scale—DAS) was evaluated in 100 adolescent dental patients (ages 13–18 years) and their parents. Parents supplied information about family demographics and their personal experiences of dental treatment. Concomitantly, the family’s behavior was observed during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Another interesting finding is that patients with lower employment and education status were more likely to indicate generalized anxiety disorders in addition to dental anxiety. Younger adults also exhibited a higher level of anxiety, which confirms previously published reports [17,18]. This finding could be related to the incomplete maturity of the prefrontal cortex, the part of the brain that rationalizes thoughts and controls emotions.…”
Section: Discussionsupporting
confidence: 89%
“…Another interesting finding is that patients with lower employment and education status were more likely to indicate generalized anxiety disorders in addition to dental anxiety. Younger adults also exhibited a higher level of anxiety, which confirms previously published reports [17,18]. This finding could be related to the incomplete maturity of the prefrontal cortex, the part of the brain that rationalizes thoughts and controls emotions.…”
Section: Discussionsupporting
confidence: 89%
“…In the Republic of Croatia, health care, including dental care, is free for children up to the age of 18, while adults pay for or have free access to health care depending on their employment status. According to Uziel et al [37], parents' education level is a significant predictor of a child's dental anxiety, with a focus on the mother's education level, although they also mention the influence of the father's education as a factor. The largest proportion (60.31%) of parents in our study had only completed high school.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported fathers’ assessments of the fear of their child or the fathers’ fear and its effect on children’s fear [ 9 , 10 , 18 , 19 , 20 , 21 ]. When studying the association between a parent’s and a child’s fear, the strength of the association varied for mothers and fathers [ 22 ]. This might reflect the fact that while both father and mother play an important role, their roles may differ.…”
Section: Introductionmentioning
confidence: 99%